Knowledge and attitude of nursing students regarding organ transplantation - Karki, S; Thapa, S; Poudyal, S (Journal of Chitwan Medical College, 2017)
Organ transplantation is the standard therapy of several end-stage diseases. Organ donation is the major component for transplant programs; however, the rate of organ donation is relatively low in Asia. In Nepal an estimated 2.8 million people have some sort of kidney ailments, while 3,000 kidney failures are reported every year. Therefore, the current study aims to identify the attitude and knowledge regarding organ transplantation. Descriptive research design was conducted using self administered questionnaire and five points Likert scale to collect information among the nursing students. The study was carried out among B.Sc. Nursing and BNS first year students at College of Nursing of Chitwan Medical College. Proportional stratified random sampling method was used to select the study sample i.e. 50 students (23 B.Sc. Nursing and 27 BN Nursing 1st year students).The data was edited, coded and analyzed using the Statistical Package of Social Sciences (SPSS) program version 17. A total of 50 nursing students, 54% were BN 1st year students and 46% were B.Sc. Nursing 1st year students. The mean age of the students was 21.98±3.384 years. The mean score obtained by students on introduction of organ transplantation was 8.54±2.39, knowledge regarding eye transplantation was 2.72±1.17 and knowledge regarding kidney transplantation was 3.58±1.44. Majority (82%) of respondents had medium level of knowledge and 94% of them had positive attitude regarding organ transplantation. This study illustrated that students had positive attitude towards organ transplantation however, low knowledge regarding organ transplantation was noted in the current study. So educational activities should be provided for the improvement of knowledge among nursing students.